Post Infarct Left Ventricular Remodeling: Current Concept in Pathophysiology and Management - Chowdhury, NA; Ullah, M; Gafur, S; Islam, Z (Cardiovascular Journal, 2011)
DOI: http://dx.doi.org/10.3329/cardio.v3i2.9199 Cardiovasc. J. 2011; 3(2): 248-253